Skin manifestations associated with systemic diseases - Part II, - Juliana Martins Leal; Gabriela Higino de Souza; Paula Figueiredo de Marsillac; Alexandre Carlos Gripp (Sociedade Brasileira de Dermatologia, 2022)
Abstract The skin, by reflecting internal processes, externalizes what happens inside the body in many diseases. Thus, the skin, as an organ, extrapolates its functions of protection, barrier and signals the existence of systemic diseases, expanding the importance of the dermatologist beyond the skin surface. Thus, the dermatologist investigates diagnostic hypotheses for conditions related to all systems and refers patients to the appropriate specialty. Combined with examination by a trained eye, the skin, due to its easy access, is still the ideal place for performing biopsies, which often clarify the diagnosis. This manuscript is the second part of the article on cutaneous manifestations of systemic diseases. In the first part, the cutaneous manifestations of the main rheumatologic and granulomatous diseases were described, and vascular manifestations were also addressed. In the present article, it will be discussed how metabolic, cardiovascular, kidney, and gastrointestinal diseases can manifest themselves in the integumentary system. Malignant diseases and their cutaneous implications, will also be discussed. Pruritus and its clinical cutaneous correspondence will be discussed. Finally, an update on cutaneous signs of SARS-CoV2 coronavirus infection will be presented.